The influence of individual readiness to change on the rise of blackberry LTD - Felix, Ben; Lee, Darren (Priviet Social Sciences Journal, 2025)
This article extensively explores BlackBerry Ltd. ’s fall and rise, charting its path from a dominant hardware production company in the mobile phone devices industry to its current focus on the software and cybersecurity industry. It delves deeply into the strategy of individual readiness to change undertaken by John Chen, the new CEO, to navigate the swiftly changing market and technological landscapes. Under the leadership of CEO John Chen, who took the helm in 2013, BlackBerry pivoted successfully toward enterprise software, particularly in the areas of cybersecurity, automotive systems, and Internet of Things (IoT) technologies. Moreover, it assesses the implications of the transformations for BlackBerry Ltd. ’s positioning in its newfound operational domains, highlighting both the challenges and opportunities that lie ahead for the company within the cybersecurity and software services sectors. This is an in-depth exploration of BlackBerry Ltd. ’s strategic evolution and John Chen's quest to transform the company's future. This analysis demonstrates BlackBerry Ltd. ’s ongoing commitment to motivating its readiness to change and embrace new opportunities in an ever-changing market.